La diaspora, instrument de la politique de puissance et de rayonnement de l’Inde à l’île Maurice et dans le monde - Anouck Carsignol-Singh (EchoGéo)
People of Indian Origin (PIOs) have, since the beginning of the XXth century, been used by the Indian intelligentsia to promote the image of the sub-continent and diffuse India’s cultural values on the international stage, as cultural ambassadors of India in their host countries. Today, the new partnership between New Delhi and the Non Resident Indians (NRIs) go beyond India’s cultural diplomacy, and the support of the Diaspora in favour of the nuclear deal plays a strategic part in the affirmation of India as an emerging power. An analysis of the mobilisation of Indo-Mauritians in line with the interests and values of India illustrates the double role of the diasporic factor in the emergence of India as a regional and global power, as a tool of New Delhi’s soft power and Realpolitik.